Ocorrência, abundância e expressão de genes associados a vias de tradução em Mimivírus e em Tupanvírus, os mais novos gigantes de amebas caracterizados - Lorena Christine Ferreira da Silva (2017)
In recent years, several DNA giant viruses have been identified. The presence of peculiar and distinct characteristics not seen in most previously known viruses, aroused interest in the scientific community regarding this group. In 2003, Acanthamoeba polyphaga mimivirus (APMV) was identified and interestingly some of the genes encoded by its large genome are related to translation process. These genes were considered exclusive of cellular organisms and have never been observed in other viruses. The biological relevance of their expression to APMV is still unknown. Currently, it is known that other giant virus isolates also present genes encoding elements involved in translation. Thus, this study aimed to prospect and characterize new giant viruses isolates in environmental samples and to increase the comprehension about the role of translation-associated genes in both new and previously isolated mimivíruses. Two viruses with morphology never seen were observed and called Tupanvirus. These viruses presenting a capsid associated to a long tail, being able to reach 2.3 μm, being the longest viral particle already observed. One of the isolates possesses the ability to multiply in a broad spectrum of protozoa cells, as some species from the Acanthamoeba genus, Vermoamoeba vermiformis and others, something never described in the literature, since the known giant viruses have a very restrict host spectrum. Full genome sequencing of the two isolated Tupanviruses was performed and showed genomes with ~1,4 mega pair bases and allowed to analyse translation-associated genes, present in abundance in these isolates. Our phylogenetic analysis emphasize that they were acquired independently of cellular organisms. Tupanviruses present the most complete set of translation-associated genes in the virosphere, with 20 aminoacyl-tRNA synthetases, 70 tRNAs and dozens of other factors associated with translation. Finally, the expression of translation-associated genes after infection with different mimivírus was assessed by real-time PCR and indicated that these are differentially expressed according to the infection conditions and genetic variances between different isolates. The data presented here contribute to a better understanding about the origin, abundance, diversity and expression of genes associated with translation, present in mimivírus and tupanvirus.